Mild cognitive impairment: The dilemma - Pinto, Charles (Medknow Publications, 2009)
Memory complaints are ubiquitous in our aging population. Many older adults fear that today’s forgetfulness will usher in tomorrow’s dementia. Mild cognitive impairment (MCI) is considered by many as an intermediary stage for dementia. Though the nomenclature has been varied and extensive, the criteria by the American Academy of Neurology and the EADC have been helpful. Prevalence rates varying from 3% to as high as 59% with a conversion rate to dementia varying from 8 to 15% only increases the need for diagnostic tests and markers which are in the form of neuropsychological tests, neuroimaging and other biological markers. Medications indicated for treatment of mild to severe Alzheimer’s Disease (AD) are offered to persons with MCI with a varying type of response which does not hold in the long run to newer strategies of exploring disease modifying drugs which hold a better promise. This benefit with management of risk factors like hypertension and diabetes coupled with non-pharmacological approaches like exercise and social networking has thrust upon us the necessity for coordinating our efforts to improve detection and management of MCI.